Metabolomics-based study of the effect of dietary N-carbamoylglutamic acid addition to heifers in late pregnancy on newborn calves - Wang, Jiandong; Yu, Youli; Guo, Yanan; Guo, Yansheng; Liang, Xiaojun (Frontiers in Veterinary Science, 2024)
It has been demonstrated that supplementing late-gestation cow diets with NCG (N-carbamoylglutamic acid) increases the serum protein level, boosts immunological function, and increases the birth weight of the calves. However, the underlying mechanism remains unclear. In this experiment, 30 late-gestation Angus heifers almost at same conditions were chosen for this experiment. They were randomly divided into two groups of 15 cows each. A basal diet was provided to the control group, and 30 g/(d-head) of NCG was added to the basal diet of the test group (NCG group). Blood samples were collected from the jugular vein after birth and before the end (when the calves were 90 days old) of the experiment for plasma metabolomics analysis. The metabolomics analysis identified 53 metabolites between the NCG group and control group, with 40 significantly up-regulated and 13 significantly down-regulated. Among them, 33 lipids and lipid-like molecules made up 57.89% of all the metabolites that were found. Thirty-three metabolic pathways enriched by metabolites showed p.adjust <0.05, among which glycerophospholipid and sphingolipid metabolism pathways were the most abundant. In conclusion, the addition of NCG in late-gestation cows appears to primarily affect calf growth and development through the regulation of phospholipid metabolism, which plays a role in nerve conduction, brain activity, and cell metabolism and function. This study provides valuable insights into how nutritional supplementation by late-gestation cows might improve the growth and development of newborn calves.